2021
DOI: 10.1080/14763141.2020.1869815
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of dry-land strength & power into thrust in competitive swimming

Abstract: The aim was to compare the transfer of dry-land strength and power (S&P) of the shoulder into thrust in front-crawl between swimmers of different competitive levels. Four elite and six sub-elite swimmers were selected to perform a dry-land or an in-water test in random order. The dry-land S&P measurements comprised mean torque, peak torque and mean power of the shoulder rotators of the dominant and nondominant upper-limbs that were assessed on an isokinetic dynamometer at 90°/s and 180°/s. In-water mean thrust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lopes et al [ 7 ] showed that resistance training on dry land with intensities between 60% and 80% of the training load improves the upper body strength (the increase in the 1RM bench press) and 50 m in the front crawl (3.98%). The gain effect of strength in water by the transfer of dry land strength and conditioning into muscle strength propulsive in front crawl swimming after 9 weeks of concurrent resistance training may be a factor that can improve all the variables related to sprint swimming performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lopes et al [ 7 ] showed that resistance training on dry land with intensities between 60% and 80% of the training load improves the upper body strength (the increase in the 1RM bench press) and 50 m in the front crawl (3.98%). The gain effect of strength in water by the transfer of dry land strength and conditioning into muscle strength propulsive in front crawl swimming after 9 weeks of concurrent resistance training may be a factor that can improve all the variables related to sprint swimming performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides task-related parameters (i.e., variables assessed during and related to actual swimming), organismic-related parameters (i.e., variables related to the swimmer itself) that are not specific to the swimming task have been indirectly correlated to swimming performance, e.g., dry-land upper-body strength [ 2 , 3 ], has been reported to be positively correlated with swimming speed. Anthropometric features, such as height [ 4 , 5 ], arm span [ 6 , 7 ], and hand surface area [ 8 ], have been reported to directly or indirectly affect swimming speed and other performance-related parameters [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exercise selected in the present study (bench press) activates a similar muscle group to that used in the front crawl [ 22 ], but may not facilitate muscle actions at a relevant speed. Recent evidence suggests that the speed of movement, as well as the performance level of swimmers, may alter the correlation with swimming speed [ 23 ]. This limitation may be partially overcome using the F–V and P–V profiles in specific dry-land exercises.…”
Section: Discussionmentioning
confidence: 99%